(untitled) (Canada Watch, 2020)
Indigenous languages play a prominent role in the academic discipline of linguistics, particularly in Canada. Linguists have worked extensively with speakers of Indigenous languages in the documentation and analysis of vocabulary, grammar, and discourse. Such work can have beneficial outcomes for both the field of linguistics and the communities in which Indigenous languages are spoken. However, it cannot be denied that the field of linguistics has often enjoyed a disproportionate share of these benefits. This brief article outlines the goals of modern linguistics, the role that Indigenous languages have played in the field, and the tensions that can exist between the different priorities of academic linguists and Indigenous communities.